Butterfly Pea Flower (Clitoria ternatea Linn.) Extract Ameliorates Cardiovascular Dysfunction and Oxidative Stress in Nitric Oxide-Deficient Hypertensive Rats - Putcharawipa Maneesai; Metee Iampanichakul; Nisita Chaihongsa; Anuson Poasakate; Prapassorn Potue; Siwayu Rattanakanokchai; Sarawoot Bunbupha; Petcharat Chiangsaen; Poungrat Pakdeechote (MDPI AG, 2021)
In this study, we examine whether Clitoria ternatea Linn. (CT) can prevent Nω-nitro-L-arginine methyl ester hydrochloride (L-NAME)-induced cardiac and vascular dysfunction in rats. Male Sprague Dawley rats were given L-NAME (40 mg/kg, drinking water) and orally administered with CT extract (300 mg/kg/day) or lisinopril (2.5 mg/kg/day) for 5 weeks. The main phytochemical components of the CT extract were found to be flavonoids. The CT extract alleviated the high blood pressure in rats receiving L-NAME. Decreased vasorelaxation responses to acetylcholine and enhanced contractile responses to sympathetic nerve stimulation in aortic rings and mesenteric vascular beds of L-NAME treated rats were ameliorated by CT extract supplementation. Left ventricular hypertrophy and dysfunction were developed in L-NAME rats, which were partially prevented by CT extract treatment. The CT extract alleviated upregulated endothelial nitric oxide synthase expression, decreased plasma nitrate/nitrite levels, and increased oxidative stress in L-NAME rats. It suppressed high levels of serum angiotensin-converting enzyme activity, plasma angiotensin II, and cardiac angiotensin II type 1 receptor, NADPH oxidases 2, nuclear factor-kappa B, and tumor necrosis factor-alpha expression. The CT extract, therefore, partially prevented L-NAME-induced hypertension and cardiovascular alterations in rats. These effects might be related to a reduction in the oxidative stress and renin-angiotensin system activation due to L-NAME in rats.